2021
DOI: 10.21203/rs.3.rs-526332/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial Activities of Coriander Seed Essential Oil and Silver Nanoparticles

Abstract: Bacterial infections are one of the most serious health problems all over the world, which cause need for the discovery of new drug. Since antibiotic resistance is a major threat to both humans and the environment, there is a need for studies on the antimicrobial properties of different forms of traditionally used plants. Herein, the seeds of coriander were used to isolate essential oil (EO) and to synthesise silver nanoparticles (C-AgNPs). The major oil constituents were characterized by GC-MS as Linalool (79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In research on the make-up of plants, the crucial active elements found in Nigella sativa are composed of thymoquinone, thymohydroquinone, dithymoquinone, p-cymene, carvacrol, 4-terpineol, t-anethole, sesquiterpene, longifolene, α-pinene, and thymol [10]; The most important active components of Cuminum cuminum are alkaloid, anthraquinone, coumarin, flavonoid, glycoside, protein, resin, saponin, tannin and steroid [11]; The most important active components of Pimpinella anisum are stated as trans-anetole, estragole, γhymachalen, para-anisaldehyde and methyl cavicol [12]. Previous studies have demonstrated that these substances possess antibacterial effects due to the active components in the plants causing damage to the cell wall and leading to cell death [13].…”
Section: Resultsmentioning
confidence: 99%
“…In research on the make-up of plants, the crucial active elements found in Nigella sativa are composed of thymoquinone, thymohydroquinone, dithymoquinone, p-cymene, carvacrol, 4-terpineol, t-anethole, sesquiterpene, longifolene, α-pinene, and thymol [10]; The most important active components of Cuminum cuminum are alkaloid, anthraquinone, coumarin, flavonoid, glycoside, protein, resin, saponin, tannin and steroid [11]; The most important active components of Pimpinella anisum are stated as trans-anetole, estragole, γhymachalen, para-anisaldehyde and methyl cavicol [12]. Previous studies have demonstrated that these substances possess antibacterial effects due to the active components in the plants causing damage to the cell wall and leading to cell death [13].…”
Section: Resultsmentioning
confidence: 99%